EASY PROOF OF PRIMARY LIMITS IN PRIVATE SCHOOLS - Erkinova Odinahon; Sulaymonova Rohilahon (Journals Park Publishing, 2024)
In this article, it is written about the proof and origin of the "Wonderful and important limits", which students of higher education institutions use and study to find the limits of functions in the science of mathematical analysis.
Keywords: limit, Lopital's rule, derivative, function, derivative of a complex function, change of form.